Determination of Factors Influencing Cultivation and Utilisation of Pumpkins Among Smallholders in Kakamega and Nyeri Counties, Kenya. Issue 1 (5th July 2019) - Kiramana, J.K.; Isutsa, D.K.
ABSTRACT: Pumpkin is becoming an important fruit-vegetable, although its potential remains unexploited in Kenya. This study aimed at enhancing conservation, preservation and production of naturalized pumpkins through the cataloguing of accessions and documentation of indigenous traditional knowledge influencing cultivation and utilization. In 2012 an expedition led to the collection of 155 accessions of Cucurbita moschata (Lam.) Poir., with 70 from Kakamega and 85 from Nyeri. Variegated accessions were significantly ( P < 0.05) the most popular and highly utilized, compared to the exotic green-leafed ones. Significantly ( P < 0.05) more green-leafed accessions were collected in Nyeri, and variegated in Kakamega. There was significant ( P < 0.05) variation in fruit shape and skin colour. Fruit-form ranged from ovate to globose or elliptical, and the predominant skin colour was dark to pale-green. Intercropping was the main cropping system. Food provision and income generation significantly ( P < 0.05) influenced cultivation and utilization of the pumpkins. Most variegated accessions were inherited from past generations and have become naturalized. The green-leafed accessions were introduced by farmers and other stakeholders. Fruits and leaves were significantly ( P < 0.05) utilized by farmers, compared to seeds and whole plants. The quality of fruits and leaves, cooking method and recipes were significantly ( P > 0.05) considered by farmers when selecting accessions to cultivate. These factors were significant ( P > 0.05) in sustaining genetic diversity and conservation. Interventions to preserve positive factors and overcome constraining ones should be promoted to enhance growing of naturalised pumpkin for good health and income generation.